The Mediation Role of Career Adaptability between Career Commitment and Career Motivation: An Empirical Investigation - Najib, Hast Haval M.; Aljanabi, Abdulqadir (Information Management and Business Review, 2020)
This study investigates the nexus between career commitment, adaptability and motivation, and the mediation role of career adaptability on the relationships between career commitment and motivation. Data were collected randomly from marketers working in the telecommunication sector in the Kurdistan region of Iraq through online questionnaires. There were 121 out of 285 forms received and analyzed using the structural equation modeling approach. The findings indicate that both career commitment and adaptability have direct effects on career motivation. Furthermore, a mediation effect of career adaptability was identified in the relationship between career commitment and motivation. The findings of the study contribute to the career motivation literature by investigating the effects of individual factors, namely career commitment and career adaptability, on career motivation in the context of developing countries. The study also points out the compound effect of these factors on career motivation.